"Me Perdía en la Escuela": Latino Newcomer Youths in the U.S. School System. Issue 2 (1st April 2020) - Szlyk, Hannah Selene; Berger Cardoso, Jodi; Barros Lane, Liza; Evans, Kerri
Abstract: Unaccompanied minors, or "newcomer youths, " come to the United States from Mexico and Central America to escape violence and persecution, and to seek financial and academic opportunities. Many newcomer youths arrive with gaps in their formal education attributed to the immigration process and the heterogeneity of their pre-U.S. lives. Once they are enrolled in the U.S. school system, many educators struggle to accommodate the academic needs of these students. Drawing on the framework of social and cultural capital, this article aimed to expand the current knowledge on the experiences of Latino unaccompanied youths in the U.S. school system. A thematic analysis of semistructured interviews with 30 newcomer students and 10 key informants revealed six themes: socialización con los demás compañeros (getting along with the other students); poca confianza (little trust); no sé lo que decían (I do not know what they were saying); it is a hard landing; education, interrupted; and estoy agradecido (I am grateful). The article offers suggestions for school social workers and educators on how to promote academic success, student resilience, and school connectedness for a vulnerable youth population.